2020
DOI: 10.1007/s10554-020-01869-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of left atrial strain with left ventricular end-diastolic pressure in patients with normal left ventricular ejection fraction

Abstract: Left ventricular diastolic dysfunction (LVDD) remains challenging to be assessed by echocardiography. We sought to explore the relationship between left atrial strain and left ventricular (LV) diastolic function in patients with normal left ventricular ejection fraction (LVEF) by invasive left-heart catheterization. 55 consecutive individuals with LVEF > 50% underwent LV catheterization. Standard transthoracic echocardiography was performed during 12 h before or after the procedure. Left atrial (LA) strain wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 23 publications
1
31
0
1
Order By: Relevance
“…Non-invasive imaging modalities have assessed LA deformation for initial diagnosis [25,[44][45][46][47], prognostic assessment [48-51], and evaluation of treatment response across different disease states [52][53][54][55]. Cardiac deformation analysis using strain and strain rate (SR) imaging allows early detection of pre-clinical cardiac disease.…”
Section: La Deformation Assessmentmentioning
confidence: 99%
“…Non-invasive imaging modalities have assessed LA deformation for initial diagnosis [25,[44][45][46][47], prognostic assessment [48-51], and evaluation of treatment response across different disease states [52][53][54][55]. Cardiac deformation analysis using strain and strain rate (SR) imaging allows early detection of pre-clinical cardiac disease.…”
Section: La Deformation Assessmentmentioning
confidence: 99%
“…Recently, LA function measured as LA reservoir strain (LASr) has been shown to be significantly related to invasive left ventricular filling pressure [ 5 , 6 , 11 ]. This was also confirmed in our study [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that left atrial (LA) strain, especially LA strain during the reservoir phase (LASr), is impaired in the setting of LV diastolic dysfunction and correlates well with LVFP or pulmonary capillary wedge pressure, suggesting that LASr is clinically useful for estimating LVFP [ 5 , 6 ]. However, in some patients with coronary artery disease, LASr is not the best parameter for discriminating the filling pressure status [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…All images were stored digitally, volume and strain analyses were performed offline using a commercially available software (QLab 10.8.0; Philip Healthcare). The LA maximum and minimum volume indices (LAVImax and LAVImin, respectively) and LA empty fraction (LAEF) were evaluated from the apical 4-and 2-chamber views by the 2-dimensional quantitative speckletracking method [11,15,16]. All images were analyzed by 2 investigators who were blinded to participants' characteristics and exercise performance.…”
Section: Echocardiographymentioning
confidence: 99%
“…However, evaluating LA phasic function by strain analysis was recently shown to be feasible and reproducible, with alterations in LA strain preceding changes in LA volume. There is evidence that LA reservoir strain combined with the ratio of transmitral E velocity to tissue Doppler mitral annulus e′ velocity (E/e′) is a useful single measure for predicting elevated LV filling pressure reflecting LV function in patients with coronary artery disease [11]. Although various LA parameters have been proposed, there is no single parameter that best defines LA function in CHF patients with reduce exercise capacity.…”
Section: Introductionmentioning
confidence: 99%